UniStatus - a cross-sectional study on the contamination of uniforms in the Danish ambulance service - Vikke, Heidi Storm (BMC Res Notes, 2015)
BACKGROUND: Patients are at risk of contracting infections due to the presence of disease-causing microorganisms that can be transmitted from the medical staff’s uniforms to the patient. The dual purpose of this study was to examine the contamination level of the uniforms worn by ambulance staff after a shift and to test the effect of washing of the uniform with and without a detergent containing acetic peroxide. METHODS: This was a cross-sectional study in which 30 ambulance staff uniforms were randomly selected for inclusion and divided into two groups. Before washing, 90 prints were performed with specific agar plates to determine bacterial contamination and to establish the prevalence of a variety of microorganisms. Group A uniforms were washed with a detergent without acetic peroxide; Group B uniforms were washed with a detergent containing acetic peroxide. RESULTS: Before washing, the 90 prints had an average colony-forming units (CFU) of potentially pathogenic bacteria of 68.89 per 25 cm(2) and a prevalence of: E. coli and Pseudomonas 0%, Bacillus cereus 27.78% (CI 95% ± 9.80), Clostridium and Enterococcus 2.22% (CI 95% ± 1.96), Staphylococcus aureus 21.11% (CI 95% ± 7.80). After washing, CFU was reduced to 3.09 (CI 95% ± 5.04) per 25 cm(2) in Group A and to 1.47 (CI 95% ± 4.77) per 25 cm(2) in Group B. The prevalence of specific bacteria in either group was 0%, except for S. aureus which had a prevalence rate of 4.40% (CI 95% ± 6.10) in Group A. The difference between the contamination degrees of the two groups was not significant in either test (p > 0.05). CONCLUSION: Potentially pathogenic bacteria are detectable on ambulance staff uniforms when a shift ends. Optimal prevention of bacterial infection may be achieved by daily changing, washing at a minimum of 60 degrees Celsius and use of a detergent containing acetic peroxide.